Absolute and pixel-wise measurements of vibration amplitudes using time-averaged digital holography. (October 2019) - Psota, Pavel; Mokrý, Pavel; Lédl, Vít; Stašík, Marek; Matoušek, Ondřej; Kredba, Jan
Highlights: Vibration amplitude was independently measured in each pixel of the image surface. Vibration amplitude can be reliably measured for shaded or discontinuous objects. Vibration amplitude distributions with high slopes can be measured. Nodal points of harmonic vibration do not need to lie within the field of view. Abstract: This paper presents scanning time-averaged digital holography, a method for measuring the amplitude distributions of harmonically oscillating objects. Each intensity image reconstructed from the time-averaged digital hologram has the form of a set of fringes that follow a zero-order Bessel function of the first kind. Modulating the phase of the light beam in the interferometer results in shifts in the bright zero-order fringes with changes in modulation depth. The developed method is based on the continuous shift in the zero-order fringe over the object surface. The magnitude of the vibration amplitude is independently evaluated for each pixel. Unlike other digital holographic vibrometry methods based on spatial phase unwrapping or fringe counting, the proposed technique can measure vibration amplitudes without the risk of fringe number confusion or 2π errors. Thus, the new method can be used to measure high-slope amplitude distributions and discontinuous/partially shaded objects. The method was experimentally verified by measuring a bending piezo actuator, and the uncertainty of the method was determined to be in the range of nanometers.